2011
DOI: 10.1016/j.aller.2010.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Th1 and th2 cytokine expression in nasopharyngeal secretions during acute bronchiolitis in children younger than two years old

Abstract: These findings show that Respiratory Syncytial Virus infection contributes to Th1 polarisation in immune response of respiratory mucosa, an effect that is similar to other environmental factors. Further studies are needed to assess immune response to other infectious causes of acute bronchiolitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…This is consistent with other studies that have suggested that children exposed to SHS have suppressed immune responses. 1820 Even using the more conservative statistical model, our study found a significant decrease in IFN-γ amongst SHS- exposed children; this is consistent with the prior finding of IFN-γ suppression in children exposed to SHS. 13 …”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with other studies that have suggested that children exposed to SHS have suppressed immune responses. 1820 Even using the more conservative statistical model, our study found a significant decrease in IFN-γ amongst SHS- exposed children; this is consistent with the prior finding of IFN-γ suppression in children exposed to SHS. 13 …”
Section: Discussionsupporting
confidence: 90%
“…In our study RSV bronchiolitis evoked a Th1 response (predominantly IFNγ elevation over IL-4) in both peripheral blood and NPA which was contrary to the above studies. Similar to our study, Flores et al 10 from Portugal reported Th1 cytokine response in nasopharyngeal secretions among infants with RSV bronchiolitis while van Schaik et al 11 have reported an increased IFNγ levels over IL-4 levels in nasopharyngeal secretions from infants with RSV infection. They also suggested the possibility of double hit hypothesis8 stressing the role of host (genetic) and environmental factors in addition to the RSV infection in deciding the cytokine response.…”
Section: Resultssupporting
confidence: 91%
“…Still, only three studies have focused on the first wheezing episode/bronchiolitis and have analyzed complete virology and children's sensitization status . These three studies used wheezing as inclusion criterion, while other bronchiolitis studies have also included crackles, and missed blood samples . At the first wheezing episode, sensitization and rhinovirus have been linked to recurrent wheezing/asthma, and rhinovirus has been linked to atopic characteristics, whereas respiratory syncytial virus (RSV)‐induced bronchiolitis has mainly not .…”
Section: Distribution Of Risk Factors At Study Entrymentioning
confidence: 99%
“…This suggests that the future asthma risk could be assessed already at the time of the first wheezing episode. However, only few studies have particularly focused on the first wheezing episode , while most bronchiolitis studies have also included crackles with or without wheezing . Bronchiolitis is classically an RSV‐induced illness in infants, whereas wheezing typically occurs in older children and is more closely linked to rhinovirus .…”
Section: Distribution Of Risk Factors At Study Entrymentioning
confidence: 99%